Microstrip Low-Pass Filter with Sharp Roll-Off Using Transformed Radial Stubs - Hayati, Mohsen; Shahbazitabar, Hossein; Hajian, Gelareh (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel microstrip low-pass filter with good characteristics, such as sharp roll-off, wide stop-band, low insertion loss and good return loss is presented. The proposed filter with a 3 dB cut off frequency at 1.19 GHz, roll-off rate equal to 218 dB/GHz and a relative stop-band bandwidth of 163.5% (referred to a suppression level of -20 dB) is designed, fabricated and measured, achieving a highest figure of meritequal to 77228. There is good agreement between the simulation and measurement results.